SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS FOR IMPROVING PHYSICAL AND TECHNICAL-TACTICAL TRAINING IN THE PROCESS OF PREPARING BASKETBALL PLAYERS (International journal of artificial intelligence, 2025)
This article analyzes the scientific and methodological aspects of the training process of athletes in the sport of basketball. The importance of modern training methods in the development of basketball players’ physical, technical, and tactical preparedness is revealed. Special attention is paid to considering age-related and individual characteristics in planning the training process. The research findings contribute to increasing the effectiveness of basketball players’ training and improving competitive performance.